Decentralized Society: Finding Web3's Soul - Weyl, E. Glen; Ohlhaver, Puja; Buterin, Vitalik (Available at SSRN 4105763, 2022)
Web3 today centers around expressing transferable, financialized assets, rather than encoding social relationships of trust. Yet many core economic activities—such as uncollateralized lending and building personal brands—are built on persistent, non-transferable relationships. In this paper, we illustrate how non-transferable “soulbound” tokens (SBTs) representing the commitments, credentials, and affiliations of “Souls” can encode the trust networks of the real economy to establish provenance and reputation. More importantly, SBTs enable other applications of increasing ambition, such as community wallet recovery, sybil-resistant governance, mechanisms for decentralization, and novel markets with decomposable, shared rights. We call this richer, pluralistic ecosystem “Decentralized Society”(DeSoc)—a co-determined sociality, where Souls and communities come together bottom-up, as emergent properties of each other to co-create plural network goods and intelligences, at a range of scales. Key to this sociality is decomposable property rights and enhanced governance mechanisms—such as quadratic funding discounted by correlation scores—that reward trust and cooperation while protecting networks from capture, extraction, and domination. With such augmented sociality, web3 can eschew today’s hyper-financialization in favor of a more transformative, pluralist future of increasing returns across social distance.